GnRH Neurons Provide Direct Input to Hypothalamic Tyrosine Hydroxylase Immunoreactive Neurons Which Is Maintained During Lactation - Bardóczi, Zsuzsanna; Wilheim, Tamás; Skrapits, Katalin; Hrabovszky, Erik; Rácz, Gergely; Matolcsy, András; Liposits, Zsolt; Sliwowska, Joanna H.; Dobolyi, Árpád; Kalló, Imre (Frontiers in Endocrinology, 2018)
Gonadotropin releasing hormone (GnRH) neurones provide neuronal input to the preoptic area (POA) and the arcuate nucleus (Arc), two regions involved critically in the regulation of neuroendocrine functions and associated behaviours. These areas contain tyrosine hydroxylase immunoreactive (TH-IR) neurones, which play location-specific roles in the neuroendocrine control of luteinizing hormone and prolactin secretion, and sexually motivated behaviours. Concerning the changes in the activity of GnRH neurones and the secretion pattern of GnRH seen under the influence of rising serum estrogen levels and during lactation, we tested the hypothesis that the functional state of GnRH neurones is mediated via direct synaptic connections to TH-IR neurones in the POA and Arc. In addition, we examined putative changes of these inputs in lactating mice and in mothers separated from their pups and presence of analogous connections in the human infundibular nucleus (Inf). Confocal microscopic and preembedding immunohistochemical studies on ovariectomised mice treated with 17β-oestradiol (OVX+E2) provided evidence for direct appositions and asymmetric synapses between GnRH-IR fibre varicosities and TH-IR neurones in the rostral periventricular area of the POA and the Arc. As TH co-localizes with kisspeptin (KP) in the POA, confocal microscopic analysis was continued on sections additionally labeled for KP. TH-IR neurones showed a lower level of co-labeling for KP in lactating mice compared to OVX+E2 mice (16.08±5.01% vs. 57.79±5.01%). Removing the pups for 24h did not alter significantly the KP production in TH-IR neurones (17.28±4.58%). The percentage of all (KP positive plus KP negative) TH cells innervated by GnRH-IR varicosities in the POA did not differ in the three animal models investigated. Similarly, the percentage of Arc dopaminergic neurones contacted by GnRH axon varicosities did not show significant differences. Relevance of these data to humans has been suggested by the confocal microscopic observation of GnRH-IR contacts on TH-IR neurones in the infundibular nucleus (Inf). This study shows evidence that GnRH neurones provide direct synaptic inputs to POA and Arc dopaminergic neurones. The scale of anatomical connectivity with these target cells was unaltered during lactation indicating a non-plastic character of GnRH input to this cell population.